Efeitos da intervenção em parentalidade positiva sobre o investimento parental de pais de crianças com autismo - Gasparini, Loyane Fassarella (2023)
Several factors can affect parental investment in offspring; however, there is still a scarcity of studies in the literature demonstrating that positive parenting interventions can increase parental investment in children with autismo. Thus, the objective was to carry out and evaluate the effect of an online group intervention in promoting positive parenting on parental investment in parents of autistic children. The intervention involved the participation of 5 mothers of autistic children aged 4 to 12 years old. The effect of the intervention was assessed through the application of pre- and post-intervention instruments, namely: Parental Investment Scale, Questionnaire of Difficulties and Resources, Parenting and Family Adjustment Scales, sociodemographic questionnaire, and the participants' reports about the intervention. The results suggest that parenting intervention can be efficient in terms of reducing negative parenting practices and improving investment in parent-child interaction. Furthermore. The pre-test results with the sample of 20 participants the results suggest that the more parents exhibit emotional maladjustment, the lower the parental investment related to care, companionship, values, emotional support, interactions, values, evocations, physical play, and the overall quality of the relationship. It is suggested that future research may investigate the effects of the intervention in a larger sample, including parents and children with different levels of autism support.